The thought of Rudolf Von Jhering and Otto Von Gierke under the perspective of two studies by Felipe González Vicén - Arjona Herraiz, Marcos (Revista de derecho aragonés, 2023)
This brief essay aims to present, and even rescue, two magnificent studies by the Spanish legal philosopher Felipe González Vicén on the concept and method of Law in the legal thought of Rudolf von Jhering and Otto von Gierke, two of the most eminent German jurists of the second half of the 19th century. Throughout this exposition, therefore, the thought of these jurists will be briefly outlined, primarily following González Vicén’s studies. The main objective of this work is to show the influence that these two jurists have had on González Vicén’s legal thinking, particularly in the development of his ideas about the concept and method of Law, as well as in the relationships between Law and the autonomous realm of ethics.